Factors influencing college students' attitude towards counseling - Legaspi, Estesa Xaris Q. (Animo Repository, 2013)
This study examined the factors influencing attitudes towards counseling of 3,039 college students in Zamboanga City. Factors included in the investigation are adherence to Asian values, perceived stigma towards seeking professional psychological help, year level. course program and type of school enrolled in, and gender. The study used the Asian Values Scale (AVS), the inventory of Attitudes Towards Seeking Mental Health Services (LASMHS) and the Stigma Scale for Receiving Psychological Help (SSRPH). The study found that contrary to previous research. adherence to Asian values was positively correlated to attitudes towards counseling, but with a weak positive correlation (r=0.06). Perceived stigma was found to have an inverse relationship with attitudes towards counseling. Education and Liberal Arts majors held significantly more positive views towards seeking counseling over students enrolled in other fields of study, as did female students over male counterparts. Year level and type of school were not found to influence attitudes towards counseling. Implications for further research were discussed.